TINJAUAN YURIDIS PEMBERIAN DAN GAGAL BAYAR DALAM PEMBIAYAAN PENDIDIKAN TINGGI SARJANA DI INDONESIA DAN DI AMERIKA SERIKAT: Legal Review of Granting and Default in Financing Higher Education in Indonesia and the United States - Shanda Amarissa; Arif Wicaksana (Reformasi Hukum Trisakti, 2025)
This study examines the application of the 5C financing principles in providing undergraduate higher education loans, comparing the advantages, disadvantages, and default resolution mechanisms in Indonesia and the United States. Indonesia refers to the Banking Act, while the U.S. follows the Higher Education Act and its derivatives. A normative legal method with a descriptive-qualitative approach was used. The findings show that both countries apply the 5C principles. However, Indonesia lacks specific regulations and institutions as found in the U.S. Therefore, establishing a dedicated legal framework is essential to prevent legal uncertainty in educational financing.